2022
DOI: 10.4055/cios22090
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Fossae Lumbales Laterales and Pelvic Incidence for Estimating Transsacral Corridors Assessed Using Reconstruction Computed Tomography

Abstract: Background The present study aimed to evaluate the effect of fossae lumbales laterales and pelvic incidence (PI) on transsacral corridors. Methods Patients who underwent pelvic computed tomography (CT) during routine therapy in a single center between 2015 and 2020 were retrospectively reviewed. The patients’ age and sex were documented during CT examination. Measurements were performed for both the upper and second sacral segments. Height and weight of the patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…On the study on whether the dimple of Venus can be utilized to evaluate and predict pelvic torsion showed that the dimple did not significantly predict pelvic torsion [22]. Balta et al [5] did not find a statistically significant relationship between the dimple of Venus and sacral anatomy in terms of sacral screw corridor. Despite being widely used, the PIA at the spinopelvic junction cannot be estimated from any anatomical landmark and physical or anthropometric examination findings [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the study on whether the dimple of Venus can be utilized to evaluate and predict pelvic torsion showed that the dimple did not significantly predict pelvic torsion [22]. Balta et al [5] did not find a statistically significant relationship between the dimple of Venus and sacral anatomy in terms of sacral screw corridor. Despite being widely used, the PIA at the spinopelvic junction cannot be estimated from any anatomical landmark and physical or anthropometric examination findings [23].…”
Section: Discussionmentioning
confidence: 99%
“…Imagama et al [ 4 ] described the relationship between low PIA and intervertebral disc degeneration. A recent study has revealed the relationship between the dimple of Venus and increased PIA [ 5 ].…”
Section: Introductionmentioning
confidence: 99%